Design of machine elements - Ramakrishna, Kamaraju (New Delhi Oxford University Press, 2017)
Design of Machine Elements provides a detailed exposition of the principal theories behind the design process and their application in various machine members, including transmission elements. It is written to cater to the students of undergraduate mechanical engineering and allied disciplines for a two-semester course on the subject.
Keywords: Mechanical Engineering